The Toyota way to continuous improvement : linking strategy and operational excellence to achieve superior performance - Liker, Jeffrey K.; Franz, James K. (New York : McGraw-Hill Irwin, 2011)
In his bestselling business management classic The Toyota Way, Jeffrey Liker introduced the world to the foundational principles that have made Toyota the envy of companies around the world. Now, in The Toyota Way to Continuous Improvement, Liker teams up with former Toyota production engineer James Franz to explain the underlying thinking behind continuous improvement and why any company needs a disciplined approach to process improvement in every part of the organization
The newest book in the bestselling Toyota Way series gives executives and managers the blueprint for successful lean process projects that deliver breakthrough results
1. Section one : the journey to continuous improvement -- 2. Section two : case studies of lean transformation through PDCA -- 3. Section three : making your vision a realty
Includes index
Keywords: Corporate culture; Industrial management; Industrial productivity; Production management